Toll signaling immune function and evolution in Anopheline mosquitoes - Rhodes, Victoria L. M. (Kansas State University, 2018)
Malaria remains a major human vector-borne disease, greatly contributing to global human morbidity and mortality. Control of mosquito vectors that transmit malaria continues to be dependent on the widespread application of chemical insecticides through indoor residual spraying and insecticide treated bed nets. However, resistance to these insecticides is spreading within many mosquito populations, adding an ever-increasing urgency to the development of alternative vector control measures. The mosquito immune system is a potential novel target for such alternative measures, as the immune response initiated in these insects during infection with vector-borne disease agents is a key determinant of vector competence and, thus, contributes to a species’ vectorial capacity. These immune responses, additionally, interact with and respond to parasitic or symbiotic biocontrol agents employed to kill or manipulate infection outcome with vector-borne disease agents. Entomopathogenic fungi, including Beauveria bassiana, have been considered as an alternative vector control measure, functioning as biopesticides. The Toll pathway is a key antifungal immune pathway in insects that impacts an insect’s ability to survive fungal infections. A better understanding of Toll signaling immune function and evolution in anophelines, both vector and nonvector, can thus help to improve future biocontrol methods of important vector mosquitoes like Anopheles gambiae. In this dissertation, I report the use of B. bassiana strain I93-825 in An. gambiae to analyze the impact of Toll pathway modulation on mosquito survival. Mosquito survivorship was strongly affected by B. bassiana exposure dose by several measured parameters including median survival, longevity, and hazard. Modulation of Toll signaling, by way of knockdown by RNA interference, revealed a dose-dependent trade-off between immune activation state and survivorship in An. gambiae. To better determine the full Toll immune signaling repertoire in mosquitoes, I annotated and describe the evolutionary history of intracellular Toll pathway members and Toll-like receptors (TLRs) within 21 mosquito genomes. The intracellular signaling pathway is conserved with 1:1 orthology, and evolutionary rates across different intracellular pathway members vary widely as compared to the conserved protein core of these mosquito species. In contrast, TLRs evolved largely by duplication events within certain anopheline lineages, most dramatically in the An. gambiae complex, where six TOLL1/5 paralogs likely possess different ligand binding specificities. Thus, these TLRs should be prioritized for experimental analyses of TLR immune function in An. gambiae. Taken together, the work in this dissertation identifies Toll pathway modulation as a potential resistance mechanism that could impact malaria biocontrol strategies and provides a foundation for future detailed studies of Toll pathway function in important mosquito vector species.
Keywords: Toll signaling; Beauveria bassiana; Anopheles